2015
DOI: 10.1039/c5nj01170a
|View full text |Cite
|
Sign up to set email alerts
|

The rhodium complex of bis(diphenylphosphinomethyl)dopamine-coated magnetic nanoparticles as an efficient and reusable catalyst for hydroformylation of olefins

Abstract: Magnetic nanoparticles(MNP) functionalized by a new bis(diphenylphosphinomethyl)dopamine(bpd) of type MNP@bpd were prepared, characterized and their reusability as catalysts were assessed by hydroformylation reaction.A new bis(diphenylphosphinomethyl) dopamine (bpd) ligand has been prepared and anchored on the surface of magnetic nanoparticles (MNPs). The obtained ligand and the surface functionalized nanoparticles of type MNP@bpd have been characterized by various analytical techniques, such as NMR, IR, TEM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…41 Encouraged by such distinctive features of having highly improved activity and excellent recyclability over the conventional support-based catalysts, we continue to contribute to the development of highly recyclable heterogeneous catalysts. 29,[42][43][44] Here, we report a "dip-catalyst" comprising Pd nanoparticles supported on bio-processed jute stem (Pd@GS), for the transfer hydrogenation of olens, quinoline and other N-heteroarenes in water (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…41 Encouraged by such distinctive features of having highly improved activity and excellent recyclability over the conventional support-based catalysts, we continue to contribute to the development of highly recyclable heterogeneous catalysts. 29,[42][43][44] Here, we report a "dip-catalyst" comprising Pd nanoparticles supported on bio-processed jute stem (Pd@GS), for the transfer hydrogenation of olens, quinoline and other N-heteroarenes in water (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our effort to develop promising catalysts for industrial applications, we recently reported magnetic‐nanoparticle‐supported catalysts of the C−C bond formation reaction. Although excellent yields were achieved for the series of olefinic substrates tested, it was difficult to carry out the multistep synthesis of the phosphinated ligands present on the support system ,. In the current paper, we report the growth of Pd nanoparticles on the robust ZIF‐8 in the presence of formic acid as a mild reducing agent and report its catalytic application to the Mizoriki‐Heck C−C bond formation reaction.…”
Section: Introductionmentioning
confidence: 98%
“…[29] Furthermore, increasing restrictions imposed by governments and the United Nations protocols with the aim of eliminating toxic chemical processes require adopting safer procedures. In this context, researchers have studied systems with metals, such as Mn, [30] Ni, [31][32][33] Ru, [34,35] Co, [36][37][38] Rh, [39][40][41] Ir, [42][43][44][45] Pd, [46,47] and Pt [48] immobilized on zeolite, [49,50] silica, [50,51] polymers, [52][53][54] alumina, [55] magnetite, [39,[56][57][58][59] and carbon. [60] These systems exhibit moderate to excellent conversion and selectivity, especially in the hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%